Thiazolidinone motif in anticancer drug discovery. Experience of DH LNMU medicinal chemistry scientific group - Lesyk, R. B.; Zimenkovsky, B. S.; Kaminskyy, D. V.; Kryshchyshyn, A. P.; Havryluk, R. B. LD. Ya.; Atamanyuk, D. V.; Subtel’na, I. Yu.; Khyluk, D. V. (Вiopolymers and Cell, 2011)
The aim was analysis of 4-thiazolidinones and related heterocyclic systems anticancer activity data and formation of some rational design directions of potential anticancer agents. Synthetic research carried out in Danylo Halytsky Lviv National Medical University (DH LNMU) allowed us to propose a whole number of new molecular design directions of biological active 4-thiazolidinones and related heterocyclic systems, as well as obtain directed library that numbers over 5000 of novel compounds. At the present time in vitro anticancer activity screening was carried out for more than 1000 compounds (US NCI protocol (Developmental Therapeutic Program), among them 167 compounds showed high antitumor activity level. For the purpose of optimization and rational design of highly active molecules with optimal «drug-like» characteristics and discovering of possible mechanism of action SAR, QSAR analysis and molecular docking were carried out. The ultimate aim of the project is creating of innovative synthetic drug with special mechanism of action and sufficient pharmacological and toxicological features. Some aspects of structure–activity relationships were determined and structure design directions were proposed. The series of active compounds with high anticancer activity and/or selectivity levels were selected. Key words: synthesis, 4-thia(imida)zolidinones, thiopyrano[2,3-d]thiazoles, anticancer activity, (Q)SAR.